Сучасний стан судово-медичного розпізнавання механізмів утворення ушкоджень при окремих видах автомобільної травми - Голубович, Леонід Львович; Голубович, А. Л.; Голубович, П. Л.; Зубко, Марія Дмитрівна; Куртєв, А. В.; Golubovich, L. L.; Zubko, M. D. (My University, 2017)
В статті викладені сучасні можливості та необхідні умови кваліфікованого вирішення питання щодо механізму травмування при конкретній автошляховій пригоді в салоні сучасного легкового автомобіля. Changes in the political, social and economic life, especially in the last twenty five years, accompanied by a significant increase in Ukraine the number of lorries and cars, which is owned by companies and organizations as well as individuals. What is more import cars are especially in demand among the population. Import and domestic cars marked are significantly differing by increasing of speed and to some extent are equipped by security measures. At the same time requirements to comply with the rules of traffic safety on the roads and measures of punishment of violators become more severe. But in spite of everything the number of road accidents is increasing every year. In the article the modem possibilities and necessary conditions for a qualified decision of the mechanism of injury at a particular motor-road accident in the cabin of the modem car are done.
Current status forensic recognition of mechanisms of damages certain species of automotive injury
Keywords: травма в салоні автомобіля; механізм ушкоджень; місце водія та пасажира; trauma in the car; mechanism of injury; the driver and passenger